Gestione delle raccolte e cooperazione nella biblioteca ibrida. Atti del convegno (Firenze, 13 ottobre 2005) - Benvenuti, Nicola (Firenze University Press, 2006)
This volume contains the proceedings of the Conference on the Management of collections and co-operation in the hybrid library, which was organised in Florence on 13 October 2005 by the Italian Libraries Association (Tuscan Section and University and Research Committee). The contributions are dedicated in particular to grasping the opportunities and adaptations generated by Internet and the possibility of disseminating electronic documents, both in the development of the collections and the planning of services and in the study of new forms of communication between institutions.